New Perspectives on Geography of Media - Peiren, SHAO. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Based on the ancient Chinese concept of the unity of Heaven and Man ($1!9(!0d'^]!0!(B, 'tian ren he yi'), guided by principles governing the connections and interdependencies between Heaven, Earth, Man, and the media, and in accord with the coexistence of these four elements in balance and in harmony, this monograph outlines the scope of the study, fundamental concepts and theories, and future directions of research in the interdisciplinary field of the geography of media. The author delves deeply into the themes of time, space, place, landscape, and scale to introduce readers to a wide array of intriguing concepts that add new dimensions to this relatively new academic field. In addition, this monograph presents a history of media geography as it has evolved in the West and in China over the past several decades, and introduces principles and values from traditional Chinese culture that shed light on the nature, direction, and significance of media studies and communication research now being conducted around the globe. Intended readership: professional scholars, graduates, and general readers. .s
Scope and Significance of Media Geography -- History and Direction of Media Geography -- Media and Space -- Media and Time -- Media and Place -- Media and Landscape -- Media and Scale -- Newspaper Geography -- Television Geography -- Internet Geography.
Keywords: Human geography; Cultural geography; Mass media; Communication; Social and Cultural Geography; Media Sociology; Media and Communication